Risk of Land Degradation: A Case Study of Phu Yen Province, Vietnam - Nga, Nguyen Thi Thu; Phuong, Pham Mai; Khanh, Nguyen Quoc; Hanh, Tong Thi; Quoc, Pham Bao; Lahori, Altaf Hussain; Yeremenko, Sergiy; Tyshchenko, Vasyl; Murasov, Rustam (Ecological Questions, 2023)
The issue of the land degradation vulnerability index (LDVI) is multifaceted, encompassing climate, soil, vegetation, policy formulation, and human actions. In Vietnam, the convergence of climatic fluctuations and human impact results in phenomena, such as soil sealing, erosion, salinization, and landscape fragmentation. These phenomena are recognized as significant triggers of land degradation. This paper seeks to present a method for assessing a land’s susceptibility to degradation by utilizing ten ecological 10 criteria: NDVI; slope; bulk density (cg/cm3); cation exchange capacity in the soil (CEC; mmol(c)/kg); Soil organic carbon stock (SOC; dg/kg), pH; Nitrogen (N; cg/kg); soil thickness (cm); soil surface temperature LST (0C); precipitation of the driest quarter (mm). The research results show that Song Hinh and Son Hoa communes are standing on the most land degradation vulnerability. Some criteria that are considered important in assessing land degradation by the analytic hierarchy process (AHP) technique are NDVI, followed by slope, nitrogen, bulk density, and soil thickness. The results of the study are consistent with records in localities that are often under pressure from drought. Extreme LDVI areas were larger identified on low mountains, slope terrain, and precipitation of driest quarter under 200mm, expanding on the agricultural areas with 40km2 total province agriculture area, followed by grassland (20.3 km2), natural forests (17.2 km2), plantation forests (8.2 km2), residences (8.2 km2), and bare land (8.15 km2). Poor land management practices, such as improper construction, inadequate water management, and lack of terracing, can contribute to soil erosion and land degradation. This LDVI assessment process can be applied to some tropical countries. The NDVI index combined with the slope, nitrogen, bulk density, and soil thickness can be exploratory indicators of land sensitivity to land degradation.